The Influence of Organizational Culture, Leadership Style, and Work Discipline on Employee Performance at PT. Demosta - Sakti Wicaksono (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study looks at how work discipline, leadership style, and organizational culture affect both group and individual employee performance at PT. Demosta Berjaya. 35 respondents were chosen using a non-probability sampling technique called saturation sampling as part of a quantitative research strategy. Validity and reliability tests, together with traditional assumption testing, were used to assess the data. The hypotheses were evaluated using t-tests, F-tests, multiple linear regression analysis, and determination coefficient analysis. The findings demonstrate that corporate culture, leadership style, and work discipline all have a simultaneous, positive, and considerable impact on employee performance. Additionally, it was discovered that each of these factors alone had a favorable and considerable impact on PT. Demosta Berjaya employees' performance. These findings demonstrate the vital significance that sustainable and successful human resource management techniques play.